Please stop blaming the driver - Valverde, Germán (2025)
With this suggestive title, Michael Bernhard begins the article he published in the journal World Highways (Bernhard, 2003). Bernhard draws attention to the tendency of the press and official spokespersons from road authorities to focus on drivers and on measures aimed at modifying their behavior as the solution to the problem of traffic accidents, often overlooking the role and responsibility that infrastructure has in many cases.